Naira - Yuan Diplomacy: A Pathway for Unlocking Nigeria’s Manufacturing Sub-Sector Potentials - Nenbee, Simeon G.; Orji, Jonah O. (Richtmann Publishing, 2021)
The fountain head for weighing one unit of a domestic currency in-terms of another within an international framework is rooted in the famous Gold Standard proposed by the Bretton Woods Institutions (BWIs). This brand of thought had since been practiced and experienced in numerous trade ties that Nigeria had had with China. Like other bilateral agreements, it sets to re-define and deepen the two countries’ economic space. Thus, this paper shed lights on Naira - Yuan Diplomacy as a Pathway for Unlocking Nigeria’s Manufacturing Sub-Sector Potentials.The manufacturing industries are engines of economic prosperity. Facilitation of job creation space and poverty reducing strategies are core values in manufacturing too. This paper conclusively presume that the exchange rate pass-through mechanism can transmit price increase and macroeconomic instability from China and supply shocks to the Nigerian economy (especially from manufactured products) when adequate provisions are not domestically taken. Furthermore, the Naira-Yuan diplomacy will increase imports from China thereby increase her foreign income since Nigeria will be spending more on Chinese manufactured products, hence, increase the national income of China. The policy implication of this finding is that the net exports of China will rise faster and add to her expansion of domestic income instead of Nigeria. The paper therefore calls upon Nigeria to be proactive in ensuring a stable trade and exchange rate policies to deepen technical innovation for local manufacturing tools to boost output rather than depending more on China. Received: 18 August 2020 / Accepted: 9 October 2020 / Published: 17 January 2021